Peran Pendidikan Jasmani Olahraga dan Kesehatan dalam membangun Karakter Siswa di SMAN 8 Banjarmasin - Sari, Wafiq Aulia; Warni, Herita; Arifin, Syamsul (Indonesian Journal of Physical Education and Sport Science, 2024)
Study purpose. Character education aims to instil positive moral, ethical and social values in students so that they can grow into individuals with integrity, responsibility and contribute positively to society. In Indonesia, character education is integrated in various subjects, including Physical Education, Sports and Health (PJOK). The purpose of this study was to determine the extent of the contribution of physical education, sport and health in improving students' character. Materials and methods. This study used a quantitative descriptive method. The population of all class X students totalling 5 classes, in class X1 totalling 32 people, X2 totalling 32 people, X3 totalling 31 people, X4 totalling 30 people and X5 totalling 30 people. With a sample size of 155 students. This sampling technique uses total sampling. The instrument used in collecting data for this study was a survey using a questionnaire distributed via google form media to facilitate data collection. Processing of collected data is processed using Microsoft Excel. Results. The results showed that the percentage of 155 students, there were 5% honest indicators, 5.23% discipline indicators, 3.06% confident indicators, 3.51% polite indicators, 4.51% meticulous and careful, 6.13% cooperation, 3.25% caring indicators, 3.98% tolerance indicators, 2.15% creative indicators, and 6.26% responsible indicators. Conclusion. It is concluded that there is an increase in student character through physical education. That the responsibility factor in students is higher than other indicators, and the cooperation factor of students also tends to follow the responsibility indicator more. The character of students in physical education can be improved from the responsibility of students the importance of maximising character education from an early age to achieve optimal results in the formation of student character.